Design System of Coffee Maker with Manual Brew Method and Coffee Sales Monitoring - Narulita Dwi Nugrahaini; Mila Kusumawardani; Abdul Rasyid (Jurnal Jaringan Telekomunikasi, 2023)
Pusat Data dan Sistem Informasi Pertanian Kementrian Pertanian claimed that in 2018 Indonesia coffee consumption has national increase of 2.49%. There is reflected by expantion of coffee shops. Menu that coffee shops offered is Manual Brew Coffee, brewed manually by the barista. If there is a lot of waiting line it will decrease barista performance to making orders. It supports the impact of income earned and get a reduction of customer satisfaction. Motivated by this, a Coffee Maker system that support to monitoring water volume, water temperature, monitor coffee sales to manage time spend for make a coffee also help barista for making a coffee. This system consists of ultrasonic sensor to monitor water stock and temperature sensor to monitor the water temperature. Application on android will display data in real time to user. Results of study obtained test value on temperature sensor with an average value difference of 0.069°C. Ultrasonic sensor test to calculate volume of water produces an error value of 1.2%. The whole system comparing the speed of making coffee between the coffee maker system and manual by barista, average time difference is 1 minute 58 seconds. The value is quite good because it does not exceed the tolerance limit of each sensor, namely ±0.5°C for the temperature sensor and 1cm for the ultrasonic sensor. The obtained value is not much different from the actual coffee dose, with a difference of 0.65gr not exceeding 1gr. The system works much faster than manual coffee brewing by the barista